The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.jacr.2021.02.022
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Breast Radiologist Wellness: Impact of Gender, Financial Loss, and Childcare Need

Abstract: Purpose: The purpose of this study was to evaluate the emotional and financial impact of coronavirus disease 2019 on breast radiologists to understand potential consequences on physician wellness and gender disparities in radiology.Methods: A 41-question survey was distributed from June to September 2020 to members of the Society of Breast Imaging and the National Consortium of Breast Centers. Psychological distress and financial loss scores were calculated on the basis of survey responses and compared across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
2
9
0
1
Order By: Relevance
“…The full survey consisted of 41 multiple-choice questions and addressed the following primary endpoints: mental health, childcare, finances, work safety, COVID-19 exposure, and patient care ( Supplementary Material ). Results related to mental health, childcare, and finances were previously reported ( 16 ). Results related to survey questions specifically addressing patient care are presented here ( Figure 1 ).…”
Section: Methodssupporting
confidence: 55%
See 1 more Smart Citation
“…The full survey consisted of 41 multiple-choice questions and addressed the following primary endpoints: mental health, childcare, finances, work safety, COVID-19 exposure, and patient care ( Supplementary Material ). Results related to mental health, childcare, and finances were previously reported ( 16 ). Results related to survey questions specifically addressing patient care are presented here ( Figure 1 ).…”
Section: Methodssupporting
confidence: 55%
“…Emerging data demonstrate that the prolonged course and widespread impact of the COVID-19 pandemic, as well as the interpersonal challenges it has caused, have negatively affected the overall wellbeing of the healthcare community ( 14 , 15 ), including that of breast radiologists ( 16 ). Breast imaging is heavily reliant on effective patient-physician communication, often in the context of assuaging anxieties related to invasive procedures and delivering bad news.…”
Section: Introductionmentioning
confidence: 99%
“…However, physicians probably connect a lower patient turnover with a fall in income that may initiate financial problems. Milch et al ( 33 ), for instance, reported increased financial difficulties and financial loss in a breast imaging community during the COVID-19 pandemic and described them per se as linked with higher levels of psychological distress. This corroborates our finding of a positive association between financial problems both before and during the pandemic and psychological distress/burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Another well‐described factor, which placed stress on and impacted the well‐being of HCWs, was managing school/childcare and working 2,5,48–53 . While some types of providers temporarily transitioned to telemedicine only and were able to clinically “work from home” while still assisting with family responsibilities, for many in PHO this was not an option given the in‐person needs of PHO patients.…”
Section: Discussionmentioning
confidence: 99%